2007
DOI: 10.2174/187152807780077318
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Phosphodiesterase 4 Inhibitors for the Treatment of Allergic Skin Diseases and Psoriasis

Abstract: The phosphodiesterase (PDE) 4 is the predominant cyclic AMP degrading enzyme in a variety of inflammatory cells including eosinophils, neutrophils, macrophages, T cells and monocytes. In addition, this enzyme is expressed in non-immune cells such as keratinocytes and fibroblasts. Highly selective PDE4 inhibitors are currently under evaluation for the treatment of asthma and/or chronic obstructive pulmonary disease. Due to the broad anti-inflammatory/immuno-modulatory action of PDE4 inhibitors, it has been prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
104
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(105 citation statements)
references
References 37 publications
1
104
0
Order By: Relevance
“…The majority of these have been developed to specifically inhibit phosphodiesterase (PDE) 4, an enzyme that exhibits increased activity in inflammatory disorders such as AD and which is central to the production of the inflammatory cytokines that elicit AD flares (45)(46)(47)(48). This more targeted approach may provide enhanced cellular control of inflammation with a reduced risk of AEs.…”
Section: Emerging Topical Therapiesmentioning
confidence: 99%
“…The majority of these have been developed to specifically inhibit phosphodiesterase (PDE) 4, an enzyme that exhibits increased activity in inflammatory disorders such as AD and which is central to the production of the inflammatory cytokines that elicit AD flares (45)(46)(47)(48). This more targeted approach may provide enhanced cellular control of inflammation with a reduced risk of AEs.…”
Section: Emerging Topical Therapiesmentioning
confidence: 99%
“…In addition, this enzyme is expressed in non-immune cells such as keratinocytes and fibroblasts. Due to the broad anti-inflammatory and immuno-modulatory action of PDE4 inhibitors, it has been proposed that PDE4 inhibitors might also be efficacious for skin disorders such as psoriasis and atopic dermatitis (Bäumer et al, 2007). These PDE4 inhibitors displayed strong anti-inflammatory action in models of allergic contact dermatitis in mice, in the arachidonic acid induced skin inflammation in mice and in ovalbumin sensitized guinea pigs.…”
Section: Phosphodiesterase 4 (Pde4) Inhibitorsmentioning
confidence: 99%
“…The determination of cytokines in skin homogenates revealed that both Th1 as well as Th2 cytokines are suppressed by PDE4 inhibitors, indicating an antiinflammatory activity in both the Th2 dominated acute phase as well as the Th1 dominated chronic phase of atopic dermatitis. Due to the suppression of Th1 cytokines, activity can also be expected in psoriasis (Bäumer et al, 2007). Consequently PDE4 inhibitors are currently in clinical development for treatment of psoriasis both topically (AN-2728 from Anacor Pharmaceuticals) and orally (CC-10004 from Celgene Corporation).…”
Section: Phosphodiesterase 4 (Pde4) Inhibitorsmentioning
confidence: 99%
“…Some examples are topical Atizoram and orally Arofylline. The newly FDA approved Roflumilast (Darilesp®) for severe COPD is being investigated for its utility in atopic dermatitis (Baumer et al 2007).…”
Section: Phosphodiesterase-4 Inhibitorsmentioning
confidence: 99%